Foreign Direct Investment In Brand Retail Sector In India: A Forecasting Approach (International Journal of Scientific Research and Management (IJSRM), 2015)
India is the tenth largest economy in the world of nominal GDP and growth rate is 5.2%. Indian Companies allowed raising equity capital in the international market through the issue of GDRs/ ADRs/FCCBs. In Indian Statistics, the FDI in India is 76%. The two stages of retail marketing is expressed with modern retailing and anti competitive behaviour. The inflow of foreign capital helps in removing the balance of payment over time. By taxing the profits of foreign enterprise, the developing countries mobilize funds for development projects. India being a signatory to World Trade Organization’s General Agreement on Trade in Services, which include wholesale and retailing services, had to open up the retail trade sector to foreign investment